CORRELATION BETWEEN DERMATOGLYPHY AND THE BASIC TYPOLOGICAL PECULIARITIES OF COLLEGE STUDENTS' CENTRAL NERVOUS SYSTEM (Fiep Bulletin - online, 2014)
For Saldanha (2002), the utilization of finger prints in the individual identification has become diffused, because clinicalmedical investigations had a great interest given the discovery of congenital anomalies determined by chromosomic mutations. Dermatoglyphy is accepted as a science's area and has either the status of prescription and prevision. About the temperament Novais apud Kalinine (2003, p.12) says that it is "the group of morphological physiological particularities that differ the individuals from each other and act on the character", and concludes, "it is the spontaneous way of being, thinking and feeling, acting and reacting of each one". This study's objective was verifying if there is a link between "dermatoglyphy" and the basic typological peculiarities of the central nervous system. The experience was made in Joaçaba-SC, at UNOESC, and involved 163 of their Physical Education Course students of both sex. It's a descriptive study, with a co relational typology. To determine the dermatoglyphic characteristics it was used the Dermatoglyphic Method proposed by Cummins and Midlo (1942), while the central nervous system basic typological peculiarities determination was made using the STRELAU's questionnaire (1984). For the statistic treatment it was used the Pearson Correlation and the significance level used was á= 0,05. The obtained results don't show any correlation among the dermatoglyphic indexes and the basic typological peculiarities of the central nervous system of the used sample, to the significance level of á= 0,05. Based on the results, it can be concluded that there is no correlation between the dermatoglyphy and the basic typological peculiarities of the central nervous system of the students involved.